Focus on French as a foreign language : multidisciplinary approaches - Dewaele, Jean-Marc, 1962- (Second language acquisition (Clevedon, England), 2005)
This book offers insights into the acquisition and use of French as a foreign language. The authors are specialists in their particular theoretical paradigms and focus on morphology, morpho-syntax, syntax, discourse, as well as fluency in the French interlanguage from beginners to advanced learners with different first languages.